Evaluation of antihyperalgesic and analgesic effects of 35% nitrous oxide when combined with remifentanil: A randomised phase 1 trial in volunteers. Issue 12 (December 2021) - Wehrfritz, Andreas; Bauer, Marcus; Noel, Nathalie; Ramirez-Gil, Juan Fernando; Ihmsen, Harald; Prottengeier, Johannes; Schüttler, Jürgen; Bessiere, Baptiste
Abstract : BACKGROUND: Remifentanil is an effective drug in peri-operative pain therapy, but it can also induce and aggravate hyperalgesia. Supplemental administration of N2 O may help to reduce remifentanil-induced hyperalgesia. OBJECTIVE: To evaluate the effect of 35 and 50% N2 O on hyperalgesia and pain after remifentanil infusion. DESIGN: Single site, phase 1, double-blind, placebo-controlled, randomised crossover study. SETTING: University Hospital, Germany from January 2012 to April 2012. PARTICIPANTS: Twenty-one healthy male volunteers. INTERVENTIONS: Transcutaneous electrical stimulation induced spontaneous acute pain and stable areas of hyperalgesia. Each volunteer underwent the following four sessions in a randomised order: 50 to 50% N2 -O2 and intravenous (i.v.) 0.9% saline infusion (placebo); 50 to 50% N2 -O2 and i.v. remifentanil infusion at 0.1 μg kg −1 min −1 (remifentanil); 35 to 15 to 50% N2 O-N2 -O2 and i.v. remifentanil infusion at 0.1 μg kg −1 min −1 (tested drug) and 50 to 50% N2 O-O2 and i.v. remifentanil infusion at 0.1 μg kg −1 min −1 (gas active control). Gas mixtures were inhaled for 60 min; i.v. drugs were administered for 30 min. MAIN OUTCOME MEASURES: Areas of pin-prick hyperalgesia, areas of touch-evoked allodynia and pain intensity on a visual analogue scale were assessed repeatedly for 160 min. RESULTS: Data from 20 volunteers were analysed. There were significant treatment and treatment-by-time effects regarding areas of hyperalgesia ( P  < 0.001). After the treatment period, the area of hyperalgesia was significantly reduced ( P  < 0.001) in the tested drug and in the gas active control (30.6 ± 9.25 and 24.4 ± 7.3 cm 2, respectively) compared with remifentanil (51.0 ± 17.0 cm 2 ). There was also a significant difference between the gas active control and the tested drug sessions ( P  < 0.001). For the area of allodynia and pain rating, results were consistent with the results for hyperalgesia. CONCLUSIONS: Administration of 35% N2 O significantly reduced hyperalgesia, allodynia and pain intensity induced after remifentanil. It might therefore be suitable in peri-operative pain relief characterised by hyperalgesia and allodynia, such as postoperative pain, and may help to reduce opioid demand. TRIAL REGISTRATION: EudraCT-No.: 2011-000966-37.